Epigallocatechin-3-gallate prevents lipid peroxidation and enhances antioxidant defense system via modulating hepatic nuclear transcription factors in heat-stressed quails - Şahin, Kazım; Orhan, C.; Tuzcu, M.; Ali, S.; Şahin, Nurhan.; Hayirli, A. (Elsevier, 2010)
Epigallocatechin-3-gallate (EGCG), a polyphenol derived from green tea, exerts antioxidant effects. Oxidative stress is one of the consequences of heat stress (HS), which also depresses performance in poultry. This experiment was conducted to elucidate the action mode of EGCG in alleviation of oxidative stress in heat-stressed quail (Coturnix coturnix japonica). A total of 180 five-week-old female Japanese quails were reared either at 22 degrees C for 24 h/d (thermoneutral, TN) or 34 degrees C for 8 h/d (HS) for 12 wk. Birds in both environments were randomly fed 1 of 3 diets: basal diet and basal diet added with 200 or 400 mg of EGCG/kg of diet. Each of the 2 x 3 factorially arranged groups was replicated in 10 cages, each containing 3 quails. Performance variables [feed intake (FI) and egg production (EP)], oxidative stress biomarkers [malondialdehyde (MDA), catalase (CAT), superoxide dismutase (SOD), and glutathione peroxidase (GSH-Px)] and hepatic transcription factors [nuclear factor.-light-chain-enhancer of activated B cells (NF-kappa B) and nuclear factor (erythroid-derived 2)-like 2 (Nrf2)] were analyzed using 2-way ANOVA. Exposure to HS caused reductions in FI by 9.7% and EP by 14.4%, increased hepatic MDA level by 84.8%, and decreased hepatic SOD, CAT, and GSH-Px activities by 25.8, 52.3, and 45.5%, respectively (P < 0.0001 for all). The hepatic NF-kappa B expression was greater (156 vs. 82%) and Nrf2 expression was lower (84 vs. 118%) for quails reared under the HS environment than for those reared under the TN environment (P < 0.0001 for both). In response to increasing supplemental EGCG level, there were linear increases in FI from 29.6 to 30.9 g/d and EP from 84.3 to 90.1%/d, linear decreases in hepatic MDA level from 2.82 to 1.72 nmol/g and Nrf2 expression from 77.5 to 123.3%, and linear increases in hepatic SOD (146.4 to 182.2), CAT (36.2 to 47.1), and GSH-Px (13.5 to 18.5) activities (U/mg of protein) and NF-kappa B expression (149.7 to 87.3%) (P < 0.0001 for all). Two-way treatment interactions revealed that the degree of restorations in all response variables was more notable under the HS environment than under the TN environment as supplemental EGCG level was increased. Moreover, levels of oxidative biomarkers were strongly correlated with expressions of hepatic nuclear transcription factors. In conclusion, supplemental EGCG alleviates oxidative stress through modulating the hepatic nuclear transcription factors in heat-stressed quails.
Keywords: epigallocatechin-3-gallate; oxidative stress biomarker; nuclear transcription factor; heat stress; Japanese quail